Bond line models of glued wood-to-steel plate joints. (15th August 2016) - Larsson, Gustaf; Gustafsson, Per Johan; Serrano, Erik; Crocetti, Roberto
Highlights: Numerical models of wood-to-steel plate joints are compared to test results. A bilinear fracture softening model is suggested if no rubber is applied. A linear elastic model can be used even though rubber is applied. The numerical analysis indicates a 150% strength increase if rubber is applied. Abstract: The competitiveness of timber as structural material in large structures is often governed by the cost of structural joints. Tests indicate that the new joint concept presented herein using glued wood-to-steel plate joints can possibly reduce the cost by matching joint strength to member strength. The design is inspired by two previously proposed designs using a single large dowel and using a rubber foil interlayer in adhesive joints. Analytical 1D and numerical 3D models of the bond line are proposed in order to further develop the concept, both in the case of a traditional adhesive joint and for the innovative rubber foil adhesive joint. The glued wood-to-steel plate joints studied are lap joints with a load bearing capacity assumed to be governed by failure within or along the bond line. In the 1D and 3D structural models both linear elastic and non-linear fracture mechanics were applied, with the non-linear fracture mechanics model taking into account the gradual damage fracture softening in a fracture zone. For the conventional type of bond line it was found that bond line softening needs to be considered for adequate strength analysis while it was not needed for a bond line with a rubber foil. The computational results are compared to previous full scale test results. The numerical results show good agreement and the analytical results reasonable agreement. When using a high strength adhesive, the strength of the wood along the bond line is governing joint failure. For this case, the analyses predict a 150% load bearing capacity increase by the introduction of a rubber foil as compared to a traditional design. The test results indicated an even higher increase.